Nutritional Requirements of Selenomonas ruminantium for Growth on Lactate, Glycerol, or Glucose - Linehan, B. (1978)
The nutritional requirements of Selenomonas ruminantium HD4 for growth on glucose, glycerol, or lactate were investigated to clarify the results of previous studies and to relate the nutrition of the organism to its physiology. The organism required l-aspartate, CO(2), p-aminobenzoic acid, and biotin for growth on a lactate-salts medium that contained small amounts of dithiothreitol. Aspartate could be replaced by l-malate or fumarate but not by succinate or l-asparagine. Requirements for growth with glycerol as an energy source were similar, except that aspartate was not required. With glucose as the energy source, neither aspartate nor p-aminobenzoic acid was required, but a requirement for volatile fatty acids, which could be met by n-valerate, was observed. CO(2) was required for growth on lactate or glycerol but not on glucose on complex media containing Trypticase and yeast extract. Sulfide could be used as the sole source of sulfur.